Effectiveness of Goat Manure and Inorganic Phosphate Fertilizers on the Growth and Yield of Mung Bean (Vigna radiata L.) - Liliek Dwi Soelaksini; Frichananta, Amalia (International Integrated Agricultural Journal (IIAJ), 2026)
The availability of phosphate in the soil is generally low, especially in soils with minimal organic matter content. This study aims to evaluate the effect of applying goat manure and inorganic phosphate fertilizer on the growth and yield of mung bean plants (*Vigna radiata* L.). The research was conducted in Antirogo Village, Sumbersari District, Jember Regency, East Java, from June to September 2024, using a factorial randomized block design (RBD) with two factors and three replications. The first factor was the dose of goat manure at 0 tons/ha, 10 tons/ha, 20 tons/ha, and 30 tons/ha, while the second factor was the dose of inorganharvested area for potatoes in 2014 was 76,291 ha, with a production of 1,347,815 tons and a productivity of 17.67 tons/ha; in 2015, the harvested area wasight, dry seed weight, shoot biomass, root biomass, and weight of 100 seeds. The results showed that the interaction of 20 tons/ha of goat manure and 200 kg/ha of inorganic phosphate produced the highest dry seed weight per plot (565.67 g), while the combination of 20 tons/ha of goat manure and 100 kg/ha of phosphate fertilizer increased shoot biomass (8.75 g). The application of 20 tons/ha of goat manure also had a significant effect on plant height (30.10 cm). This increase is thought to be due to the improved availability of phosphate because of adsorption by organic matter, allowing nutrients to be more easily absorbed by the plants.